2011
DOI: 10.1111/j.1439-0507.2009.01801.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of sertaconazole nitrate 2% cream vs. miconazole in patients with cutaneous dermatophytosis

Abstract: Sertaconazole is a new antifungal agent. To compare the efficacy and tolerability of sertaconazole and miconazole cream in cutaneous dermatophytosis, this prospective, randomized, multicentric comparative, phase 4 study was undertaken in 260 patients with cutaneous dermatophytosis after approvals from Institutional Ethics Committees. Patients were assigned to sertaconazole cream (2%) or miconazole cream (2%) topically twice daily for 2 weeks after obtaining informed consent. Efficacy variables included changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 8 publications
(14 reference statements)
0
22
0
1
Order By: Relevance
“…A study by Sharma et al, has shown that the sertaconazole produced 62.3% clearance at the end of 2 weeks. 22 In the study by Alomar et al, 95.6% clinical cure rate was seen at the end of treatment with sertaconazole. 23 Mycological assessment with KOH mount showed that at the end of "treatment phase," 94% patients treated with sertaconazole 2% cream and 62% patients who received clotrimazole 1% cream were negative for fungal elements.…”
Section: 21215mentioning
confidence: 93%
See 1 more Smart Citation
“…A study by Sharma et al, has shown that the sertaconazole produced 62.3% clearance at the end of 2 weeks. 22 In the study by Alomar et al, 95.6% clinical cure rate was seen at the end of treatment with sertaconazole. 23 Mycological assessment with KOH mount showed that at the end of "treatment phase," 94% patients treated with sertaconazole 2% cream and 62% patients who received clotrimazole 1% cream were negative for fungal elements.…”
Section: 21215mentioning
confidence: 93%
“…Sharma et al have reported five patients in the sertaconazole group and nine in the miconazole group developing mild to moderate adverse events. 22 del Palacio et al have reported premature termination of their trial due to adverse effects, which were 26.7% with clotrimazole 1% cream in candida and dermatophyte skin infections.…”
Section: 21215mentioning
confidence: 99%
“…Sertaconazole nitrate is a broad-spectrum third-generation [36]. It is a fungicide with long skin perdurability (up to 72 h), which is one of the properties that makes it different from other imidazoles.…”
Section: Candidiasis Associated With Diaper Dermatitismentioning
confidence: 99%
“…The most widely used antimycotics are clotrimazole, miconazole and ketoconazole [42, 43]. Ciclopirox [35, 43] and sertaconazole [36] are also effective. It is important to note that nystatin and mupirocin are not effective against dermatophytosis [19].…”
Section: Dermatophytosis In the Diaper Areamentioning
confidence: 99%
“…Differences in the species which are the agents of CBM have been observed, depending on the region. F. pedrosoi is related to humid areas of a tropical and subtropical climate, whereas C. carrionii is dominant in a semi-arid climate [37, 39, 42, 50, 61]. It is particularly visible in Madagascar where in the tropical rainforest area in the north of the island, F. pedrosoi is prevalent, whereas in the south of the island with the “thorny desert” climate, Cladophialophora carrionii is more common [44, 62].…”
Section: Geographical Distributionmentioning
confidence: 99%